Arahan Penggunaan Lahan Berbasis Kemampuan Lahan Menggunakan Metode Land Classification and Landuse Planning - Nurul Ainun Tangge; Tri Mulya Hartati; Sri Asmirani Idris; Dahri Nengkeula (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Maliforo Village, Central Halmahera District, has land that has the potential to be developed into an agricultural area considering its fertile area. However, the land cannot be optimized properly, and is at risk of agricultural failure. The objectives of this study are: 1) to determine the distribution of land capability classes; 2) to determine the factors that influence land capability classes; and 3) to determine the direction of land use based on land capability. This study uses a free survey method where observations and measurements are carried out directly in the field. While the identification of physical characteristics of the soil uses boring and profile techniques to determine the evaluation of land capability. The Land Classification and Landuse Planning (LCLP) method is also used in this study. The results of the study showed 1) the distribution of land capability is grouped into five classes with class III as the largest area with an area of ​​96.5 ha (45.8%); 2) factors that influence land capability are slope gradient, erosion level and landslide hazard; 3) land use direction in Maliforo Village that is suitable for agricultural development is in land capability class III-L with a gentle slope of 96.5 ha, namely for extensive agricultural development.